Investigation of Biodegradation and Biocompatibility of Chitosan–Bacterial Cellulose Composite Scaffold for Bone Tissue Engineering Applications - Somchai Yodsanga; Supattra Poeaim; Soranun Chantarangsu; Somporn Swasdison (Cells, 2025)
Developing scaffolds with a three-dimensional porous structure and adequate mechanical properties remains a key challenge in tissue engineering of bone. These scaffolds must be biocompatible and biodegradable to effectively support osteoblastic cell attachment, metabolic activity, and differentiation. This study successfully fabricated a chitosan-bacterial cellulose (CS-BC) composite scaffold using the solvent casting/particle leaching (SCPL) technique, with NaOH/urea solution and sodium chloride crystals as the porogen. The scaffold exhibited a well-distributed porous network with pore sizes ranging from 300 to 500 µm. Biodegradation tests in PBS containing lysozyme revealed a continuous degradation process, while in vitro studies with MC3T3-E1 cells (pre-osteoblastic mouse cell line) demonstrated excellent cell attachment, as observed through SEM imaging. The scaffold also promoted increased metabolic activity (OD values) in the MTT assay, and enhanced alkaline phosphatase (ALP) activity and upregulated expression of osteogenic-related genes. These findings suggest that the CS-BC composite scaffold, fabricated using the SCPL method, holds great potential as a candidate for bone tissue engineering applications.
Keywords: Bone Tissue Engineering Materials; Electrospun Nanofibers in Biomedical Applications; biodegradable polymer synthesis and properties